Menakar Ulang Konsep Poligami dalam Perspektif Hadis : Antara Keadilan dan Kemaslahatan - Syukri, Syukri; Rahman Sakka, Abdul; Ismail Ahmad , La Ode (JISH: Jurnal Ilmu Syariah dan Hukum, 2026)
This article reexamines the concept of polygamy in Islam through the perspective of hadith, focusing on the principles of justice and public welfare (maṣlaḥah). Polygamy is often understood in a legalistic manner as a male privilege, yet in practice it frequently generates gender injustice and social problems within the family. This study employs a qualitative library research method using a thematic (mawḍūʿī) approach to hadiths related to polygamy and justice in family relations. The data are analyzed through content analysis by considering both normative religious texts and contemporary social realities. The findings reveal that the hadiths of the Prophet Muhammad (peace be upon him) consistently emphasize justice and compassion as the fundamental requirements of polygamy, encompassing both outward responsibilities and moral-spiritual dimensions. Polygamy, therefore, is not an absolute right but a serious trust that can only be justified when it truly realizes justice and welfare. This study concludes that polygamous practices leading to injustice contradict the objectives of Islamic law (maqāṣid al-sharīʿah), and thus the interpretation of polygamy should shift from mere legal permissibility toward an ethical framework grounded in justice and mercy.